The Effectiveness of Several Plant Extracts to Induce Rice Plant Resistance against Bacterial Leaf Blight - (Xanthomonas oryzae pv. oryzae) - Fitri Widiantini; Avissa Ayuningdiyas; Endah Yulia; Tarkus Suganda (Universitas Gadjah Mada, 2019)
Resistant plants are one of the disease control techniques that considered to be effective. Resistant plants can be produced in various ways including the application of plant extracts. The aim of this study was to examine the ability of several plant extracts to increase the resistance of rice plants to bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo). A total of 13 plants were extracted and applied in two methods, which were seed treatment and seedling treatment which sprayed on two-week old rice seedlings. Xoo bacteria were inoculated on rice plants two weeks after planting. The observations on the intensity of BLB disease infection showed that water hyacinth extract (Eichhornia crassippes), spiny amaranth (Amaranthus spinosus) and jasmine leaves (Jasminum grandiflorum) can suppress the development of BLB disease in both application methods. The application of plant extracts as inducing agents needs to be repeated to maintain the activated plant defense mechanism.